The effects of emotional work on job burnout with the mediating role of work-family conflict among nursing staff - Akbar Bahmani; Farshid Aslani (Shahrekord University of Medical Sciences, 2021)
Background and aims: Nurses are at risk for job burnout (JB) due to the characteristics of their work. The aim of this study was to evaluate the effects of emotional work (EW) on JB with the mediating role of work-family conflict (WFC) among nursing staff. Methods: This was an applied survey. Study population consisted of all 195 nursing staff of Imam Khomeini hospital, Bandar Turkman, Iran. Participants were 129 nursing staff selected through stratified random sampling. The Haag Emotional Work Scale, the Maslach Burnout Inventory, and the Mousavi and Alvani's WFC questionnaire were used for data collection. Data were analyzed through the structural equation modeling and confirmatory factor analysis performed via the SPSS (v. 22.0) and the AMOS (v. 22.0) software. Results: EW had significant effects on JB (path coefficient: 0.57) and WFC (path coefficient: 0.27). WFC also had significant effects on JB (path coefficient: 0.74) and had significant mediating effects on the EW-JB relationship. Conclusion: Strategies to boost nursing staff's morale can reduce their stress, JB, and WFC.